2018
DOI: 10.1002/cssc.201800583
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Dehydrogenation of Formic Acid on CdS Nanorods through Ni and Co Redox Mediation under Mild Conditions

Abstract: Selective release of hydrogen from formic acid (FA) is deemed feasible to solve issues associated with the production and storage of hydrogen. Here, we present a new efficient photocatalytic system consisting of CdS nanorods (NRs), Ni, and Co to liberate hydrogen from FA. The optimized noble-metal-free catalytic system employs Ni/Co as a redox mediator to relay electrons and holes from CdS NRs to the Ni and Co, respectively, which also deters the oxidation of CdS NRs. As a result, a high hydrogen production ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Figure S4b shows that pure CdS NRs has stable activity for H 2 evolution for only 6hours.A fter that, the H 2 production rate was significantly decreased and no significant increase was observed for H 2 production after 10 hours.T his poor performance of CdS NRs can be attributed to the fast charge recombination and photocorrosion owing to the photogenerated holes. [28] These results showed that the present photocatalytic system is highly active and robust compared to pure CdS NRs under the same conditions.…”
Section: Photocatalytic Stabilitysupporting
confidence: 53%
See 2 more Smart Citations
“…Figure S4b shows that pure CdS NRs has stable activity for H 2 evolution for only 6hours.A fter that, the H 2 production rate was significantly decreased and no significant increase was observed for H 2 production after 10 hours.T his poor performance of CdS NRs can be attributed to the fast charge recombination and photocorrosion owing to the photogenerated holes. [28] These results showed that the present photocatalytic system is highly active and robust compared to pure CdS NRs under the same conditions.…”
Section: Photocatalytic Stabilitysupporting
confidence: 53%
“…Without the Fe-salen catalyst, ap oor H 2 evolution rate of 34 mmol h À1 was observed owing to the rapid recombination of photogenerated electron-hole pairs.H owever,i nt his case,t he CO evolution rate was higher than the H 2 evolution rate,which could be attributed to the presence of Cd 2+ ions generated by photocorrosion of CdS. [28] These Cd 2+ ions were further reduced to Cd 0 as an active catalyst for CO production. [25] When complex 3 was employed, the H 2 evolution rate increased to 300 mmol h À1 ,p roving that the Fe-salen complex is an efficient catalyst that effectively suppresses charge recombination.…”
Section: Photocatalytic Co Evolution Activitiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Without the Fe–salen catalyst, a poor H 2 evolution rate of 34 μmol h −1 was observed owing to the rapid recombination of photogenerated electron‐hole pairs. However, in this case, the CO evolution rate was higher than the H 2 evolution rate, which could be attributed to the presence of Cd 2+ ions generated by photocorrosion of CdS . These Cd 2+ ions were further reduced to Cd 0 as an active catalyst for CO production .…”
Section: Resultsmentioning
confidence: 75%
“…Besides, the Fe catalyst can also capture electrons from the oxidized formate species, which enhances the possibility of protons being reduced. Furthermore, the Fe catalyst can also suppress the leaching of Cd ions from CdS . Thus, the H 2 evolution rate is much higher than the CO evolution rate in the presence of the Fe catalyst.…”
Section: Resultsmentioning
confidence: 99%